The Role of Economic Diplomacy in the System of Modern International Economic Relations - Kukharyk, Viktoriia V.; Nübling, Thomas (Mukachevo State University, 2021)
The modern globalised world is characterised by economic independence, which is a component that measures the level of relations between countries, the content, direction and intensity of which has begun to be influenced by economic dependence. In other words, economic relations have become central to diplomatic activity, which determines the relevance of the subject matter. The purpose of this study is to determine the role of economic diplomacy in the system of modern international economic relations, to compare the theoretical model of economic diplomacy and the practice of its implementation. This paper uses the following methods: scientific abstraction; monographic, dialectical, historical logical; structural logical; abstract-logical; methods of regression analysis; synthesis; problem-oriented method; statistical and graphic methods. The author used a Scatter plot model and performed a regression analysis to determine which free trade area (Ukraine-EU, Ukraine-Canada, or Ukraine-Israel) affects Ukraine's GDP growth. The study model confirms the positive relationship between Ukraine's GDP growth and the growth of foreign trade turnover (FTT) between Ukraine and the EU. The linear model explains that a 1% increase in FTT affects an average 5% increase in Ukraine's GDP. At the same time, the regression model shows the opposite trend in terms of FTT between Ukraine and Canada, Ukraine and Israel. Thus, the dynamicsof Ukraine's FTT with these countries does not have a significant impact on GDP. Only the growth of FTT between Ukraine and the EU indicates the effectiveness of bilateral cooperation. The practical significance of the results obtained lies in the fact that the theoretical foundations, conclusions, and recommendations obtained and formulated by the author can serve as a basis for further study of issues of economic diplomacy and for the development of such a concept of economic diplomacy, which should take into account the positions of stakeholders to balance the interests of ensuring the national economic security of the state.
Keywords: economic diplomacy; free trade area; economic security; national interests; 339.9